Implementation of the KEDAFIT Program to Risk Screening and Foot Health Maintenance Among Older Adults at Posyandu Bersatu Samarinda (JURNAL PENGMAS KESTRA (JPK), 2025)
Foot complications in elderly people at risk of diabetes are a health problem that can potentially lead to ulcers, circulatory problems, and even amputation if not detected early. This condition is exacerbated by the elderly's lack of knowledge in self-care and limited foot screening services at the community level. Therefore, structured promotive and preventive interventions are needed to improve early detection and maintenance of elderly foot health at the integrated health post (Posyandu) level. This activity is designed to expand the knowledge of older adults and develop the competencies of cadres in screening and maintaining foot health through the implementation of the KEDAFIT (Control, Education, Diet, Activity, and Foot Examination) Program. This community service method is implemented using a health education approach and screening assistance. The program is implemented through coordination stages, counseling using posters, videos, modules, blood sugar checks, foot observations, Ankle Brachial Index (ABI) measurements, and cadre assistance. Descriptive analysis was conducted to assess changes in participants' knowledge and health status. The results of the activity showed an increase in elderly knowledge regarding foot care from 33% to 72% after the implementation of the KEDAFIT program. Health screening identified 31 elderly people with blood sugar levels ≥126 mg/dL and 13 with ABI values ​​≤0.90. Participants demonstrated high enthusiasm, and cadres successfully performed the screenings independently after mentoring. The program also faced challenges in the form of varying physical conditions among elderly people and a limited duration. The Kedafit program has proven effective in increasing knowledge, screening skills, and awareness of elderly people regarding foot health maintenance, thus potentially becoming a sustainable intervention model Posyandu.